2017
DOI: 10.1002/mnfr.201600653
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol attenuates mitochondrial dysfunction in the liver of intrauterine growth retarded suckling piglets by improving mitochondrial biogenesis and redox status

Abstract: RSV may have beneficial effects in improving hepatic mitochondrial function and redox status in the IUGR piglets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 45 publications
8
41
0
Order By: Relevance
“…The findings of this study revealed a decrease in the final BW, liver weight, hepatic DNA concentration, protein-to-DNA ratio, and proliferation index with a decrease in the hepatic apoptotic cell number in IUGR suckling lambs compared to the NBW lambs and IUGR lambs supplemented with either L-Arg or NCG. Similar observations (e.g., impaired growth rate and liver weight) were observed in IUGR models of rats, pigs, and lambs [36,42,43]. Impaired liver growth in IUGR animal models has been linked to the general retardation in fetal somatic growth [44][45][46][47].…”
Section: Discussionsupporting
confidence: 61%
“…The findings of this study revealed a decrease in the final BW, liver weight, hepatic DNA concentration, protein-to-DNA ratio, and proliferation index with a decrease in the hepatic apoptotic cell number in IUGR suckling lambs compared to the NBW lambs and IUGR lambs supplemented with either L-Arg or NCG. Similar observations (e.g., impaired growth rate and liver weight) were observed in IUGR models of rats, pigs, and lambs [36,42,43]. Impaired liver growth in IUGR animal models has been linked to the general retardation in fetal somatic growth [44][45][46][47].…”
Section: Discussionsupporting
confidence: 61%
“…In addition, this study showed that resveratrol treatments increase both mitochondrial mass and mtDNA contents during osteogenic differentiation in PO-MSCs. These findings indicate that resveratrol can up-regulate mitochondrial biogenesis during osteogenic differentiation of PO-MSCs and are consistent with other reports regarding mitochondrial biogenesis by resveratrol in various cell types (26,(38)(39)(40)(41)(42). Moreover, the up-regulation of mitochondrial biogenesis by resveratrol in PO-MSCs is in line with the notion that metabolic shift from glycolysis to mitochondrial OXPHOS occurs during stem cell differentiation (16,17,(43)(44)(45)(46)(47).…”
Section: Discussionsupporting
confidence: 92%
“…1D). Moreover, mitochondria, which is essential to energy metabolism, was also linked with IUGR [36]. In the current study, mitochondrial DNA content and ATP activity were both significantly decreased in adult IUGR pigs (p < 0.05), as shown in Fig.…”
Section: Differential Phenotypes Between Iugr and Normal Pigsmentioning
confidence: 53%